Pertumbuhan dan efisiensi pakan ayam broiler betina yang diberi pakan mengandung metionin cukup dan disuplementasi betain - Adi Ratriyanto; Susan Dikta Mentari (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
Betaine is a methyl group donor that can increase protein synthesis since it has a similar role as methionine. The study was performed to determine the supplementation effect of betaine in the diet containing adequate methionine on growth performance and feed efficiency of female broilers. In total, 200 of day-old chicks of female broiler chickens were allotted to 4 treatments with 5 replicationsof 10 birds. This experiment was designed as completely randomized design. Control diet was formulated to contain adequate methionine (0.50% for starter and 0.38% for finisher period). The other dietary treatments were obtained by supplementing 0.1%, 0.2% and 0.3% betaine. The variables observed consisted of feed, protein and energy consumption, average daily weight gain, feed efficiency, protein and energy efficiency ratio. Supplementation of 0.1% betaine generated a higheraverage daily weight gain (P<0.05), but supplementation at higher levels (0.2 and 0.3%) had no effect on weight gain. However, betaine did not affect feed, energy and protein consumption, as well as feed efficiency and energy and protein efficiency ratio. Thus, betaine can be applied in the diet containing adequate methionine at the level of 0.1% to produce higherdaily weight gain without affecting feed efficiency. Supplementation of betaine at higher levels than 0.1% did not show positive effect on weight gain and feed efficiency in female broiler chickens.